2022
DOI: 10.1021/acs.est.2c06290
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Permanganate Activation under UVA-LED Irradiation: Unraveled Mechanism Involving Manganese Species and Hydroxyl Radical

Abstract: Permanganate [Mn­(VII)] has gained broad attention in water treatment. However, its limited reactivity toward some refractory micropollutants hinders its application for micropollutant degradation. Herein, we introduced UVA-LED photolysis of Mn­(VII) (UVA-LED/Mn­(VII)) to degrade micropollutants (diclofenac (DCF), 4-chlorophenol (4-CP), atrazine, and nitrobenzene) by selecting DCF and 4-CP as target micropollutants. The effects of operating conditions (e.g., light intensity, radiation wavelengths, pH, and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…In terms of pollutant degradation, UV-LEDs are not commonly used at a large scale in water treatment, and the comparison of lower-power UV-C to high-power UV-A wavelengths becomes important because LEDs are gaining attention . Most studies on UV-LED degradation are on the effect of wavelengths on photocatalytic degradation of emerging contaminants or UV-based advanced oxidation, with only some studies on direct photolysis of pharmaceuticals . These studies show that different wavelengths could be effective for different compounds, but they either compare only two wavelengths, only one contaminant, or do not report findings on byproduct formation and quantum yields.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of pollutant degradation, UV-LEDs are not commonly used at a large scale in water treatment, and the comparison of lower-power UV-C to high-power UV-A wavelengths becomes important because LEDs are gaining attention . Most studies on UV-LED degradation are on the effect of wavelengths on photocatalytic degradation of emerging contaminants or UV-based advanced oxidation, with only some studies on direct photolysis of pharmaceuticals . These studies show that different wavelengths could be effective for different compounds, but they either compare only two wavelengths, only one contaminant, or do not report findings on byproduct formation and quantum yields.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, because methyl phenyl sulfoxide (PMSO) can be more rapidly oxidized to PMSO 2 by Mn(V) and Mn(VI) than by Mn(VII) via the oxygen transfer pathway, it was commonly used as a probe compound for Mn(V) and Mn(VI). 5 As illustrated in Figure S6, the oxidation rate of PMSO by KMnO 4 was not accelerated in the presence of MoS 2 and WS 2 in a wide pH range of 3.0− 11.0. The results manifested that Mn(V) and Mn(VI) were not generated in the KMnO 4 /MoS 2 and KMnO 4 /WS 2 systems.…”
Section: Identification Of the Dominantmentioning
confidence: 84%
“…Water pollution induced by trace organic contaminants (TrOCs) has attracted worldwide attention due to its harmful impact on the human health and ecological environment. With the advantages of stability, low cost, ease of handling, and less formation of toxic byproducts, permanganate (KMnO 4 ) has been used as a mild oxidant for decades in water treatment, especially degrading contaminants containing electron-rich moieties, like phenolic, amine, and olefinic compounds. , But compared with that of other oxidants (e.g., ozone, ferrate, and chlorine), the reactivity of KMnO 4 is low and depends on the structure of organics, requiring higher dosages and an extended reaction time. , Very recently, several strategies have been deployed to enhance the KMnO 4 oxidation efficiency via a series of activation methods, such as energy activation (e.g., UV, solar light, and electrolysis) and chemical activation [e.g., bisulfite, humic acid (HA), and biochar]. The “activated KMnO 4 ” can decompose into massive highly reactive Mn intermediates in short time scales, such as Mn­(III), Mn­(V), and Mn­(VI), thus greatly promoting the oxidation rate of target TrOCs.…”
Section: Introductionmentioning
confidence: 99%
“…However, no apparent absorbance peaks at wavelengths of 610 nm or 660 nm were observed in the E-Mn­(VII) process (Figures S9 and S11), in agreement with the observation by Zhu et al Moreover, methyl phenyl sulfoxide (PMSO) was commonly used as a probe compound to identify the presence of Mn­(VI) and Mn­(V) because PMSO could be converted to methyl phenyl sulfone (PMSO 2 ) by high-valence Mn intermediates with a stoichiometric ratio of 1:1. ,, As shown in Figure , Mn­(VII) alone could fast transform PMSO into PMSO 2 , with the yield of PMSO 2 [η­(PMSO 2 )] approaching 100%, in agreement with previous studies. , However, the combination of electrolysis and Mn­(VII) resulted in a decrease of the PMSO transformation rate as well as the PMSO 2 formation rate. Considering that Mn­(VI) and Mn­(V) were much more reactive compared to Mn­(VII) , and they could considerably accelerate the degradation of organic pollutants if formed, the significant slow-down of PMSO oxidation indicated the absence of Mn­(VI)/Mn­(V) in the E-Mn­(VII) process. In addition, the decreased PMSO oxidation in the E-Mn­(VII) process compared to that by Mn­(VII) oxidation suggested that electrolysis accelerated the decomposition of Mn­(VII) to MnO 2 , but the resulting MnO 2 was unable to catalyze the oxidation of PMSO.…”
Section: Resultsmentioning
confidence: 99%
“…46,47 However, the combination of electrolysis and Mn(VII) resulted in a decrease of the PMSO transformation rate as well as the PMSO 2 formation rate. Considering that Mn(VI) and Mn(V) were much more reactive compared to Mn(VII) 21,48 and they could considerably accelerate the degradation of organic pollutants if formed, the significant slow-down of PMSO oxidation indicated the absence of Mn(VI)/Mn(V) in the E-Mn(VII) process. In addition, the decreased PMSO oxidation in the E-Mn(VII) process compared to that by Mn(VII) oxidation suggested that electrolysis accelerated the decomposition of Mn(VII) to MnO 2 , but the resulting MnO 2 was unable to catalyze the oxidation of PMSO.…”
Section: Dcf Degradation In Various Oxidation Processesmentioning
confidence: 99%